VLSI design of an irregular LDPC decoder in DTMB - CHEN Yun; ZENG Xiao-yang; LIN Yi-fan; XIANG Bo; DENG Yun-song (Tongxin xuebao)
An irregular LDPC decoder with a code length of 7 493 bits for DTMB system was implemented based on SMIC 0.13μm CMOS process.A new method to control memories was proposed,which can reuse memories for three different code rates only by increasing 5% memory usage.The throughput of the LDPC decoder is up to 150Mbit/s with the max iterative number of 15.While keeping the throughout of 50Mbit/s,its max iterative number can reach 45.The FPGA synthesis reports and the decoder layout in SMIC 0.13μm CMOS technology are given.